Alpha-decay induced shortening of fission tracks simulated by in situ ion irradiation. (15th April 2021) - Li, Weixing; Cheng, Yuanyuan; Feng, Lei; Niu, Jingjing; Liu, Yingxin; Skuratov, Vladimir A.; Zdorovets, Maxim V.; Boatner, Lynn A.; Ewing, Rodney C.
Highlights: Shrinkage of latent tracks during in situ ion irradiation is observed and quantified. Rather than alpha-particles, alpha-recoils induce significant track-shrinkage. Zircon is more sensitive than apatite to alpha-recoil-induced track-shrinkage. The etchable lengths of latent fission tracks can be estimated as a function of α-dose. Alpha-recoil-induced track shortening must be considered in natural zircon. Abstract: The diffusion of defects (e.g., vacancies and interstitials) and elements used for dating (e.g., He and Pb) in a mineral structure is a thermal process: This is the primary assumption used to determine the age and thermal history of minerals. For instance, thermal history reconstruction, through the number and length distribution of tracks produced by spontaneous fission of 238 U, is obtained by assuming a thermal event to be the only energy source for shortening of fission tracks. Here, we report a new, non-thermal energy source that induces additional shortening of fission tracks by the irradiation of alpha-recoils from the alpha-decay of 238 U and 232 Th. We simulate alpha-decay induced track-shortening by combining ion accelerator irradiations with transmission electron microscopy. This allows for the first observation of track-shrinkage during in situ ion irradiation. We show that rather than alpha-particles, alpha-recoils induce a significant shortening of fission tracks by nuclear-collisions. The shortening of track-length can be quantified as a function of alpha-decay event dose. However, apatite is less sensitive than zircon to this non-thermal process. The findings exemplify the interactions among different types of self-irradiation from alpha-particles, alpha-recoils and fission-fragment nuclei in single mineral grains and have important implications for the use of zircon and apatite for radiometric dating and thermochronology.